Development of synbiotic ice cream from goat milk - Robins, Ajisha; Radha, K (Indian Journal of Dairy Science, 2020)
Synbiotic ice cream was developed from goat milk by using inulin as a prebiotic and Lactobacillus plantarum (UBLP-40) as a probiotic. The treatment mix was formulated to contain more than 10% fat, 8.6% milk solids not fat, 2% inulin, 15% sugar, 0.4% stabilizer-emulsifier combination and Â probiotic Lactobacillus plantarum culture. Physico-chemical, microbiological and sensory qualities of control and synbiotic ice cream were compared. Synbiotic ice cream showed higher whipping ability (p